(untitled) (Third Sector Social Economic Review, 2020)
The purpose of this study was to determine the relationship between the loneliness perceptions and social media usage and to investigate the perception of loneliness and social media usage among individuals aged 65 and over, who are considered to be disadvantaged in many ways. The research data were collected from 293 elderly who use social media and live in Çankaya/Ankara. The data were collected using the ""Loneliness Scale"" and ""Social Media Usage Scale"". The relational model was used in the study. The data were analyzed using descriptive statistics and Pearson Correlation Analysis. According to the results, perceptions of loneliness and social media usage levels of the elderly were at a middle level. As a result of the Pearson Correlation Analysis in this sample, it was observed that there was no significant relationship between the perception of loneliness of the elderly and their usage of social media.